Analisis Tingkat Kepuasan Pengunjung terhadap Fasilitas Objek Wisata The Nickrisnally Strawberry Kabupaten Rejang Lebong - Nurhasanah Nurhasanah; Dwita Prisdinawati; Anadiya Pingki; Mira Yanuarti (Lembaga Pengembangan Kinerja Dosen, 2025)
This research was conducted in May-August 2025. The location of the research is at The Nickrisnally Strawberry Tourism. Jl. Raya Curup, Sumber Bening Village, Selupu Rejang District, Rejang Lebong Regency. This study aims to determine visitor satisfaction with the facilities of The Nickrisnally Strawberry tourist attraction in Sumber Bening Village, Rejang Lebong Regency. The sampling method in this study used the Slovin formula. Respondents in this study were visitors to The Nickrisnall Strawberry Tourist Attraction, so in determining the number of samples using the Slovin formula, the number of respondents or samples in this study was known that the population was 100 people each month. The data analysis method used in this study is descriptive quantitative analysis and data processing is carried out using the help of the SPSS (Statistical program for social science) and Microsoft Excel applications which are presented in the form of tables and tabulations, then data measurements are carried out with visitor satisfaction tools, namely Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The results of the analysis of visitor satisfaction levels using the Importance Performance Analysis (IPA) method show that the attributes that need to be maintained are attributes that fall into quadrant II. The results of the Customer Satisfaction Index (CSI) analysis were 77.29%, which means that visitors to The Nickrisnally Strawberry in Rejang Lebong Regency are satisfied with the facilities provided by the Strawberry garden tour.